Mapping evidence from systematic reviews regarding adult attachment and mental health difficulties: a scoping review. (20th July 2017) - Mullen, G.
Abstract : Objective: The aim of this scoping review was to map evidence gathered through systematic reviews regarding adult attachment and mental health difficulties. This review highlights established, emerging, and inconsistent findings, suggesting areas for future research, and implications for theory and practice. Methods: A systematic search for meta-analyses and systematic reviews measuring adult attachment and concerning mental health difficulties was conducted. In total, 17 studies met the selection criteria. Results: Findings were presented according to four identified themes, (1) measurement of attachment; (2) measurement of mental health difficulty; (3) intrapersonal processes related to attachment and mental health difficulties; and (4) interpersonal processes related to attachment and mental health difficulties. Conclusions: This review highlights the connection between attachment style and mental health difficulties, and suggests that relationships can facilitate both mental health and illheath. However, the mechanisms through which insecure attachment confers risk for mental health difficulties require further research.